Optimizing Reproductive Health Capacity: A P-Process and CBR Approach in Karang Taruna Tambak Sumur Sidoarjo - Eko Teguh Pribadi; Sri Hidayati L (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2023)
Adolescent Reproductive Health (ARH) remains a behaviorally-based health issue prioritized by government interventions, with the principal determinants being a lack of information and education on reproductive health, shifts in adolescent behavior, inadequate health services, and unsupportive regulations. The community service conducted in Tambaksumur Village, Sidoarjo District in 2023, was structured around the integration of the P-Process model and Community Based Research (CBR) aimed at enhancing adolescents' knowledge and attitudes related to ARH, and at formulating approaches for internalizing the functions of health promotion and education within the Karang Taruna organization. The service outcomes indicated that through peer-education activities, there were significant differences in the knowledge and attitudes of the targeted adolescent group before and after the intervention, with 2-tailed significance values of 0.010 (knowledge) and 0.020 (attitude). The sustainability of Karang Taruna's ARH-focused programs can be maintained through the integration of the Adolescent Posyandu program with Karang Taruna, coupled with continuous support and guidance from health academics.